2011
DOI: 10.1182/blood-2011-08-372854
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab therapy in T-cell prolymphocytic leukemia: comparing efficacy in a series treated intravenously and a study piloting the subcutaneous route

Abstract: Intravenous alemtuzumab is an effective and well-tolerated treatment for T-cell prolymphocytic leukemia (T-PLL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 11 publications
0
63
2
Order By: Relevance
“…Two patients initially resistant to alemtuzumab had overall survival of 34.3 and 12+ months (patients 1 and 7, respectively), compared to an expected survival of 4 months in such patients. (5, 42) Patient 2 who had relapsed after initial alemtuzumab therapy had an overall survival of 17 months, compared to expected survival of between 7.5 to 10 months. Patient 8 was also treated after initial alemtuzumab relapse and has survived 23.7+ months.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients initially resistant to alemtuzumab had overall survival of 34.3 and 12+ months (patients 1 and 7, respectively), compared to an expected survival of 4 months in such patients. (5, 42) Patient 2 who had relapsed after initial alemtuzumab therapy had an overall survival of 17 months, compared to expected survival of between 7.5 to 10 months. Patient 8 was also treated after initial alemtuzumab relapse and has survived 23.7+ months.…”
Section: Discussionmentioning
confidence: 99%
“…Nine of the patients treated first-line were enrolled on a pilot study to evaluate the subcutaneous route of administration of alemtuzumab. 22 Although data from CLL suggest that subcutaneous alemtuzumab has equal efficacy compared with intravenous administration, we found that this was not the case in T-PLL. The pilot study was terminated early because of the dramatic decrease in response rates associated with the change to subcutaneous administration.…”
Section: How I Treat Patients Requiring First Therapymentioning
confidence: 36%
“…Intravenous alemtuzumab results in overall response rates (ORR) in excess of 90% with 81% CRs when given to previously untreated patients with T-PLL (Table 3). 22 The ORR fell to only 33% when the antibody was administered subcutaneously. It was possible to rescue a proportion of these patients by switching to intravenous administration and/or adding pentostatin, but 2 of 9 patients died on treatment.…”
Section: How I Treat Patients Requiring First Therapymentioning
confidence: 99%
“…Despite responses to chemo/immunotherapy (alemtuzamab 11,12 with/without pentostatin, 13 hematopoietic cell transplantation, 14 fludarabine/mitoxantrone/cyclophosphamide, 15 or methylpredinisolone 16 and other alkylators), 17 the median progression-free survival (8-12 months) and overall survival (20-24 months) in T-PLL remain dismal. 18 Longer survival is seen with hematopoietic cell transplantation; however, 33% to 47% of patients relapse within 36 months and treatment-related mortality is almost as high.…”
Section: Resultsmentioning
confidence: 99%